upaya Upaya Pencegahan Perkawinan Anak Sesuai dengan Undang-Undang Nomor 16 Tahun 2019 - Anindi Lu`luil Maknun (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2023)
Child marriages that have a negative impact must be prevented through preventive measures. In order for the prevention efforts to be carried out properly, efforts must be made by all elements. Child marriage will be discussed using a qualitative method based on library research. Thus, this research results in efforts to prevent child marriage and so that it can be understood and implemented by readers.